2020
DOI: 10.3390/molecules25153322
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Polyphenols-Loaded Polymeric Nanoparticles in Cardiovascular System

Abstract: Numerous studies document an increased production of reactive oxygen species (ROS) with a subsequent decrease in nitric oxide (NO) bioavailability in different cardiovascular diseases, including hypertension, atherosclerosis, and heart failure. Many natural polyphenols have been demonstrated to decrease ROS generation and/or to induce the endogenous antioxidant enzymatic defense system. Moreover, different polyphenolic compounds have the ability to increase the activity/expression of endothelial nitric oxide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 160 publications
(196 reference statements)
0
21
0
Order By: Relevance
“…A recent study has suggested that curcumin blocks LPA-induced MCP-1 expression via TGFBR1/ROCK signaling pathway [ 103 ].Additional studies are required to improve or add meaningful insights into our understanding of the mechanism(s) of action of curcumin against atherosclerosis, especially in the clinical setting. In addition, the development of novel drug delivery systems, such as the creation of curcumin nanomicelles [ 104 , 105 ], is critical for improving the oral bioavailability of curcumin which may contribute to its clinical efficacy [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested that curcumin blocks LPA-induced MCP-1 expression via TGFBR1/ROCK signaling pathway [ 103 ].Additional studies are required to improve or add meaningful insights into our understanding of the mechanism(s) of action of curcumin against atherosclerosis, especially in the clinical setting. In addition, the development of novel drug delivery systems, such as the creation of curcumin nanomicelles [ 104 , 105 ], is critical for improving the oral bioavailability of curcumin which may contribute to its clinical efficacy [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are required to improve or add meaningful insights into our understandingof the mechanism of the action of curcumin against atherosclerosis in mice and human patients. In addition, the development of novel drug delivery systems, such as the creation of curcumin nanomicelles [84,85], is critical for improving curcumin oral bioavailability [86].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin-like plant compounds have been shown to be beneficial to the cardiovascular system due to their antiatherogenic, anti-inflammatory, anticoagulative and antihypertensive effects (Deng et al 2020 ; Pechanova et al 2020 ; Sato and Mukai 2020 ). The AIN-93M diet is a flavonoid-deficient diet.…”
Section: The Possible Cardioprotective Effects Of Quercetin-like Plant Flavonoids As Cofactors Of Cox-2mentioning
confidence: 99%